Validation of Sugar Determination In The FCV Tobacco Leafe Using Fenol-Sulfat Method By Spektrofotometer UV-Visible - Saroh, Siti; Nilam Kusuma, Maritha (Green Publisher Indonesia, 2022)
Virginia Flue Cured Tobacco is one of the type a lot of tobacco cultivated in Indonesia, Tobacco this many used as ingredient raw cigarette cigarettes, pipe tobacco and tobacco Susur (chewing tobacco). Leaf tobacco contain many compound very decisive chemistry the quality and taste of the resulting cigarettes, one of which is is sugar. Sugar content in tobacco give mild taste in cigarettes, but if rate too tall precisely will causes burning and irritation esophagus. However Thus, in SNI-01-4401-2006 it is not yet formulated method testing total sugar content. On research this conducted validation determination total sugar content in FCV tobacco with method phenol-sulfate by UV-Vis spectrophotometry aimed at get valid method for determination total sugar content of Virginia Flue Cured tobacco. Validity method showed through the parameters of linearity, precision, determination of LOD and LOQ, and accuracy. Test started with hydrolysis tobacco use sour 4.5% sulfate. Solution extract be read with UV-vis spectrophotometer at a wavelength of 490 nm with dye phenol-sulphate. Linearity test results curve obtained value of r = 0.9997 in the range work 20 – 100 mg/L, accuracy test results with 7 repetitions obtained the value of % recovery is 98.19 – 101.62%, LOD and LOQ test results respectively of 1,009 mg/L and 3,362 mg/L, while precision test results obtained deviation relative standard of 1.025%, result this still under the value of 2/3 CVH is 1.86. From the results of the t-test obtained score tcount of 0.85, the result this moresmall from table ie 2.18. Validation result method for all parameters tested has Fulfill condition acceptance so that method phenol sulfate could used in determining rate glucose FCV tobacco routine